Green Synthesis, Characterization, and Application of Ascophyllum Nodosum Silver Nanoparticles - Mishra S.K.; Sinha S.; Singh A.K.; Upadhyay P.; Kalra D.; Kumar P.; Tiwari K.N.; Singh R.; Singh R.K.; Kumar A.; Tripathi A.; Chauhan B.S.; Srikrishna S. (My University, 2025)
Purpose: Green nanotechnology as a field has emerged and gained popularity amongst biologists due to its cost-effective and environment-friendly advancements. The most preferred is the biological method which involves plants and their extracts. Methods: The silver nanoparticles were synthesized by a sunlight-driven aqueous extract (AE) of whole plant powder of Ascophyllum nodosum. Advanced techniques like high-resolution scanning electron microscopy (HRSEM), energy dispersive X-ray (EDX), high-resolution transmission electron microscopy (HRTEM), and particle size analysis were used to determine the nature of nanoparticles. Antioxidant, anti-fungal, and anti-leishmanial activities were evaluated. Result: The techniques confirmed the formation of spherical particles of the desired range of size. Silver nanoparticles exhibited a much greater DPPH (2,2-diphenyl-1-picryl-hydrazine-hydrate) radical scavenging activity which was almost six to seven folds more than that exhibited by the AE alone. The anti-leishmanial and cytotoxic activities were evaluated on Leishmania donovani promastigote and amastigote. Conclusion: The synthesized AgNPs showed remarkable DPPH radical scavenging ability owing to their antioxidant properties. The anti-leishmanial activity was exceptionally viable in both AE and AgNPs. The findings all together support the tendency of Ascophyllum nodosum to efficiently synthesized AgNPs which could be utilized for its anti-leishmanial properties. Graphical Abstract: [Figure not available: see fulltext.] © 2023, The Author(s), under exclusive licence to The Regenerative Engineering Society.